2018
DOI: 10.4236/wjet.2018.63031
|View full text |Cite
|
Sign up to set email alerts
|

Development of Risk Index of Uninterrupted Traffic Flow According to the Occurrence of Fog

Abstract: The driver's visibility is degraded when weather conditions deteriorate, which affects the traffic flow and induces traffic congestion or accidents. In particular, traffic accidents can be led to chain reaction collisions, with high rate of fatality, when fog occurs in contrast to other weather factors that may restrict visibility. For the development of a traffic risk index, a deviation of the vehicle's speed was set for the traffic risk index by referring to previous study results. In addition, factors that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The regression model of deaths due to road accidents in fog at different hours in Guilan between 2014 and 2018 revealed that the mortality rate at 2 AM (IRR = 0.05 and p = 0.005), 9 AM (IRR = 0.06 and p = 0.012), 11 AM (IRR = 0.045 and p = 0.004), 13 (IRR = 0.230 and p = 0.008) and 19 PM (IRR = 0.04 and p = 0.003) were signi cantly lower. Hours 1,3,4,5,6,7,8,10,12,14,15,16,17,18,21,22,23, and 24 could not be investigated due to the incomplete information. Also, the same model indicated a remarkable decrease in the rate of injuries at 2 AM (IRR = 0.2 and p = 0.032), 3 AM (IRR = 0.075 and p = 0.019) and 2 PM (IRR = 0.1 and p = 0.02).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The regression model of deaths due to road accidents in fog at different hours in Guilan between 2014 and 2018 revealed that the mortality rate at 2 AM (IRR = 0.05 and p = 0.005), 9 AM (IRR = 0.06 and p = 0.012), 11 AM (IRR = 0.045 and p = 0.004), 13 (IRR = 0.230 and p = 0.008) and 19 PM (IRR = 0.04 and p = 0.003) were signi cantly lower. Hours 1,3,4,5,6,7,8,10,12,14,15,16,17,18,21,22,23, and 24 could not be investigated due to the incomplete information. Also, the same model indicated a remarkable decrease in the rate of injuries at 2 AM (IRR = 0.2 and p = 0.032), 3 AM (IRR = 0.075 and p = 0.019) and 2 PM (IRR = 0.1 and p = 0.02).…”
Section: Resultsmentioning
confidence: 99%
“…In another study, the rate of fatality was 6.9% on foggy days which was the highest rate compared with 1.9% on sunny, 2.5% on rainy, and 2.5% on snowy days (7). Furthermore, according to reports, the mortalities due to multi-vehicle chain crash are more likely to occur in foggy and snowy conditions (7), with a risk ratio (RR) of 6 times for rainy, 158 for snowy and 171 for foggy weather (8).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations